Humidity-controlled interactions and lifting of MoS2 on SiO2 - Sebastiaan Haartsen; Jantinus Wisman; Harold J W Zandvliet; Pantelis Bampoulis (JPhys Materials)
Fabrication of 2D material devices under ambient conditions faces challenges from humidity-dependent interfacial interactions and doping effects due to intercalated water layers. This study explores adhesion and force dynamics for a monolayer of molybdenum disulfide (MoS _2 ) on silicon dioxide (SiO _2 ) as a function of humidity, using atomic force microscopy (AFM). At low humidity (<10%RH), capillary forces dominate due to a liquid bridge forming between the AFM tip and sample. At intermediate humidity 40%RH, an additional water layer intercalates between the MoS _2 and the SiO _2 and the capillary force model alone is insufficient to describe the tip-sample interactions. Force-distance spectroscopy reveals additional force dynamics related to MoS _2 -lifting and dynamics in the intercalated water. Above 60%RH, water condenses on the MoS _2 and the capillary interactions are reduced. Understanding and identifying these interactions is crucial for optimising deposition of 2D materials under humid conditions.